Horny for COVID: The Growth of Coronavirus Erotica. Issue 1 (1st April 2022) - Kendal, Evie
Abstract : The COVID-19 global pandemic has significantly disrupted people's social lives and dating habits. Research has shown a substantial increase in the consumption of erotic and pornographic material during periods of isolation, including narratives focused on quarantine, illness, and even the personification of the SARS-CoV-2 virus itself as a potential sexual partner. This article considers the latter manifestation of coronavirus-related erotica, focusing on the four-part e-book series, Kissing the Coronavirus, by M. J. Edwards. This article will demonstrate that as a speculative fiction subgenre, works of erotica are worthy of scholarly examination as individual texts, avoiding the tendency to consider such works only in bulk. Kissing the Coronavirus provides an insight into the confusing realities of living during a global pandemic in which knowledge about the virus rapidly changed and fear of infection and continued isolation were constant stressors impacting health and wellbeing.